PENGARUH PEMBERIAN TERAPI AKUPRESSUR TERHADAP MUAL MUNTAH PADA IBU HAMIL TRIMESTER I DI PMB H KECAMATAN CIPUTAT KOTA TANGERANG SELATAN - Redjeki, Sri (Journal of Midwifery Tiara Bunda, 2023)
Background Behind : The physiological changes experienced by pregnant women consist of changes in the reproductive system, circulatory system, respiratory system, digestive system, endocrine system, integumentary system, and hormonal system. Symptoms that appear in early pregnancy include amenorrhea , nausea and vomiting, breasts feeling full and sensitive, frequent urination, feeling weak and tired, weight gain and mood swings. Nausea and vomiting or in medical language it is called emesis gravidarum or morning Sickness is a state of nausea that is sometimes accompanied by vomiting (frequency less than 5 times). According to the Health Department's profile (2016) in Renityas (2019), it is said that based on the results of research in Indonesia, data on pregnant women with nausea and vomiting reached 14.8% of all pregnancies with complaints of nausea and vomiting occurring in 60-80% in primigravida and 40-60%. % in multigravidas. According to Jannah (2019), nausea and vomiting is a normal thing that occurs at early pregnancy and will end in the first 20 weeks of pregnancy. This complaint occurs in 70% - 80% of all pregnant women. Research Objectives : Knowing the Effect of Giving Acupressure Therapy on Nausea and Vomiting in Pregnant Women in the First Trimester in PMB H, Ciputat District South Tangerang City in 2023. Research Method : Type of research carried out use namely Pre Experiment Design using one groups pre-posttest controls groups design . Research results : p- Value is 0.000 < α (0.05), then data H 0 is rejected and Ha a is accepted. Conclusion: Giving therapy acupressure influential to nauseous vomiting on mother First tri- mester pregnancy in PMB H sub-district Ciputat, South Tangerang City.